2010
DOI: 10.1542/peds.2008-3369
|View full text |Cite
|
Sign up to set email alerts
|

Male Gender Is Associated With Intraventricular Hemorrhage

Abstract: Compared with girls, VLBW male newborns are at greater risk to develop IVH and severe IVH but not PVL. The association of male gender with IVH or severe IVH is stronger with higher BWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 31 publications
4
40
1
1
Order By: Relevance
“…Regarding to sex, as described in other studies [25], males were the majority in the case group. This association possibly reflects improved neurovascular maturation and better regulatory mechanisms in the female fetus, with more strength to hormonal influences on the maturity of the female brain, compared with the male brain.…”
Section: Discussionsupporting
confidence: 63%
“…Regarding to sex, as described in other studies [25], males were the majority in the case group. This association possibly reflects improved neurovascular maturation and better regulatory mechanisms in the female fetus, with more strength to hormonal influences on the maturity of the female brain, compared with the male brain.…”
Section: Discussionsupporting
confidence: 63%
“…The difference is reversed in adults, with cerebral blood flow higher in females than in males (Gur et al 1982;Rodriguez et al 1988;Gur RE and Gur RC 1990). The higher blood flow that we measured in male premature and term newborns is of particular interest because male infants are more at risk for disability, handicap, and mortality than females (Brothwood et al 1986;Elsme´n et al 2004;Mohamed and Aly 2010). In addition to higher blood flow, when comparing for gender differences, we found larger right--left asymmetry of CBF i in males than in females.…”
Section: Discussionmentioning
confidence: 57%
“…Other reports suggest that male sex is a risk factor for poor outcome in premature infants. Additionally, some studies have indicated a higher rate of hemorrhage in boys than in girls [15,16]. …”
Section: Discussionmentioning
confidence: 99%